História e cinema: criação e reforço do estereótipo do muçulmano e árabe - Reis, Ariana Rodrigues (2023)
Films and series are increasingly getting popular in the digital and technological environment, allowing them to reach a greater number of viewers. With greater visibility and reach, it allows presenting, in its plots, a still unknown context, thus seeking, facilitating and presenting new knowledge. Those are species of art that can teach us a lot about the world and the different cultures that exist in it. The present work proposes cinematographic analyzes of eastern and western films and series, comparing the different perspectives and approaches about the creation of stereotypes of Arabs and Muslims, which distort their identities through misstated and prejudiced representations, making comparisons between the origins of films and series and how each one portrays the Orient, punctuating both a western and an eastern view. The research is based on bibliographic reviews, contributing to the audiovisual analysis, transiting in interdisciplinarity, not only approaching History, but Philosophy, Psychology, Geography and Sociology. Thus, it was verified that the stereotype that falls upon the Middle East, was not only present in the 20th and 21st centuries, but since the beginning of the creation of cinema plots are constructed through the distortion of the different, resulting in mischaracterization of their cultural, social and regional identities. From these results we can conclude that the creation and reinforcement of the stereotype about this region originates from economic and political interests, as a demonstration of domination over those made inferior by an imperialist foreign policy